Education news. Computerized adaptive testing for the national certification examination. - Bergstrom BA (AANA Journal, 1996)
Beginning April 8, 1996, the national certification examination will be administered as a computerized adaptive test (CAT). This article explains the psychometric principles upon which CAT is based and shows examples of adaptive tests.